"It's All About Time": Time as Contested Terrain in the Management and Experience of Domiciliary Care Work in England. Issue 5 (25th February 2015) - Rubery, Jill; Grimshaw, Damian; Hebson, Gail; Ugarte, Sebastian M.; Cooke, Fang Lee; Bartram, Timothy
<x xml:space="preserve">Abstract</x> Drawing on a multilevel study of commissioning, employers, and care staff, this article explores the role of time in the management of domiciliary care work for older adults in England and the consequences for the employment conditions of care staff. An index of fragmented time practices among 52 independent‐sector domiciliary care providers reveals widespread tendencies to use zero‐hours contracts and limit paid hours to face‐to‐face contact time, leaving travel time and other work‐related activities unpaid. Care staff interviews reveal how fragmented time creates insecurities and demands high work engagement. Time management practices are shown to derive directly from strict time‐based local authority commissioning. Subcontractors, both independent small firms and those belonging to national chains, can at best adopt human resource (HR) policies that are partial routes to failure, as evident in widespread recruitment and retention problems. Informal HR practices to accommodate working‐time preferences help to retain individual staff, but adjustments are often marginal, adversely affect other staff and fail to expand the recruitment pool for social care. Labor shortages are likely to persist as long as workers are required to adapt to a regime of fragmented time and to work more hours than are paid, even at pay rates close to the national minimum wage. © 2015 Wiley Periodicals, Inc.